Research on fault location model of overhead line and cable hybrid power supply line - Jielian, Cui; Weihua, Sun; Yuqi, Cui; Xueming, Wang; Youquan, Su; Jinshuai, Wang; Yang, Yu; Chengran, Fang (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
Aiming at the problem that the overhead cable hybrid line spans complex terrain and is easily affected by natural factors such as bad weather and human factors such as piling construction, a double-ended asynchronous fault location equation is established by regarding joint resistance and fault distance as unknown quantities, in this paper. At the same time, the multi-scale quantum harmonic oscillator algorithm is used to solve the fault location, so that the line operation and maintenance personnel can find it in time and take effective measures to restore the power supply to ensure the safe and stable operation of the power system.